Efektivitas Jingle Sebagai Media Promosi Kesehatan Terhadap Keterampilan Cuci Tangan Pakai Sabun Pada Siswa SD Di Samarinda - Azzahra, Shabila Fauziah; Palin, Yona; Chifdillah, Nino Adib (Yayasan Jompa Research and Development, 2025)
Diarrhea in children is a global health problem. The number of cases of illness and death due to diarrhea in children increases every year. Handwashing with soap is a basic preventive measure in preventing diarrhea. This study aims to analyze the effect of health education using jingle media on Handwashing skills in students at SDN Loa Janan Ilir 009. This study is a pre-experimental study with a one-group pretest-posttest design. The intervention was conducted through health education using jingle media. The study sample consisted of 88 second-grade students at SDN Loa Janan Ilir 009, selected using total sampling technique. Data were collected through questionnaire completion. The research data were statistically tested using the Wilcoxon test. The results showed that the number of students skilled in practicing CTPS increased by 67 students (76.1%). Statistical analysis revealed that there was an effect of health education using jingle media on respondents' knowledge (ρ-value = 0.000). Jingle is effective as a health education medium for CTPS among elementary school students.